Clinical Course of SARS CoV-2 Infection in Hospitalized Pregnant Patients - Ansari, Asma; Siraj, Asifa; Khan, Sumaira; Jalil, Rabiya; Choudary, Abeera; Khalil, Hafsa (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the clinical course and outcome of hospitalized pregnant patients with laboratory confirmed SARS CoV-2 (COVID-19) infection Study Design: Prospective longitudinal study Place and Duration of Study: Obstetrics Units of Pak Emirates Military Hospital and Combined Military Hospital, Rawalpindi Pakistan, from May to Jun 2020. Methodology: All patients reporting for childbirth were tested for SARS-CoV-2, and those testing positive were included. The primary outcome was virus clearance time and categorization according to the severity of the disease into asymptomatic,mild, moderate, severe and critical. Furthermore, a comparison was made between the presence of comorbid conditions and symptoms in the category of COVID-19. In addition, neonatal sample evaluation for SARS-CoV-2 was done. Results: Out of the 881 women giving birth, 41(4.6%) tested positive for SARS Cov-2. Majority were asymptomatic 28(68.3%)followed by mild 8(19.5%), moderate 4(9.8%) and severe 1(2.4%) category. There was a significant association of the COVID categories with symptoms (p-value<0.005) and comorbid condition (p-value<0.001). The mean virus clearance time was 8.20±1.66 days. During hospital stay 34(82.9%) delivered. All 34(100%) delivered babies had no evidence of vertical transmission. Conclusion: Pregnant women with COVID-19 infection have a nearly similar clinical course to non-COVID women in this study. There is also no evidence of vertical transmission to the neonate.